Information Campaign on Arsenic Poisoning: Unintended Consequences in Marriage Market - Shyamal Chowdhury; Prachi Singh (Institute of Labor Economics (IZA), 2023)
Unintended consequences of public policies, while common, are under-studied and often unaccounted for in economic analysis. In this paper we study the unintended consequences of a public information campaign on water quality on the marriage market in rural Bangladesh. Despite being heavily contaminated with arsenic, groundwater was the main source of drinking water for rural dwellers in Bangladesh since the 1970s. This created a major health emergency in the country as arsenic exposure causes multiple health problems, ranging from skin lessons to various types of cancer. However, until the mid 1990s, the contamination remained largely unknown and became public knowledge only later through a nationwide information campaign. We study the impact of the campaign on marriage patterns in rural Bangladesh. Using a difference-in-difference model, we analyse the age at marriage, bride price agreed at the time of marriage and find that both of them decreased in arsenic affected areas compared to areas unaffected by arsenic contamination. The effect on age at marriage is primarily driven by younger cohorts who got married earlier. Additionally, we find an increase in the likelihood of females having their first child at an early age (between 16 to 20 years). These are important social consequences, however, often ignored in most analyses.
Keywords: I12; J12; R11; 330; arsenic contamination; health shock; information campaign; age at first marriage; bride price; age at first birth; Bangladesh